The Joy Luck Club - Tan, Amy. (New York : Penguin Books, 2006)
In 1949, four Chinese women--drawn together by the shadow of their past--begin meeting in San Francisco to play mah jong, invest in stocks and "say" stories. They call their gathering the Joy Luck Club--and forge a relationship that binds them for more than three decades.
Feathers from a thousand Li away -- The twenty-six malignant gates -- American translation -- Queen mother of the western skies.
Keywords: Women -- Societies and clubs -- Fiction; Reminiscing in old age -- Fiction; San Francisco (Calif.) -- Fiction; Chinese American women -- Fiction; Mothers and daughters -- Fiction; Loss (Psychology) -- Fiction; Female friendship -- Fiction; Mothers -- Death -- Fiction; Domestic fiction